Role for the obesity-related FTO gene in the cellular sensing of amino acids. - Gulati, P; Cheung, M; Antrobus, R; Church, C; Harding, H; Tung, Y; Rimmington, D; Ma, M; Ron, D; Lehner, P; Ashcroft, F; Cox, R; et al. (2013)
SNPs in the first intron of FTO (fat mass and obesity associated) are strongly associated with human obesity. While it is not yet formally established that this effect is mediated through the actions of the FTO protein itself, loss of function mutations in FTO or its murine homologue Fto result in severe growth retardation, and mice globally overexpressing FTO are obese. The mechanisms through which FTO influences growth and body composition are unknown. We describe a role for FTO in the coupling of amino acid levels to mammalian target of rapamycin complex 1 signaling. These findings suggest that FTO may influence body composition through playing a role in cellular nutrient sensing.